Associations of appetitive behaviors in 7-year-old children with their cardiometabolic health at 10 years of age - Warkentin, S (2020)
Background and Aims Atherosclerosis begins early in life, thus optimal cardiovascular health needs to be promoted early. We investigated whether appetitive behaviors among 7 year olds are associated with their cardiometabolic health years later. Methods and Results A sample of 2951 children from a Portuguese birth cohort was analyzed. The Children's Eating Behavior Questionnaire assessed eating behaviors, and a measure of cardiometabolic risk (higher risk group: those in the upper quartile of triglycerides, homeostatic model assessment-insulin resistance, waist circumference and systolic blood pressure and in the lower quartile of high-density lipoprotein cholesterol z-scores) was created. Linear and logistic regressions were run. Children with more food avoidant behaviors had lower cardiometabolic risk (Satiety Responsiveness – boys: OR = 0.39, 95% CI 0.16; 0.93, girls: OR=0.37, 95% CI 0.17; 0.82 and Slowness in eating – boys: OR = 0.49, 95% CI 0.25; 0.95, girls: OR = 0.49, 95% CI 0.27; 0.91). Food approach behaviors (Food responsiveness (CEBQ-FR), Enjoyment of food (CEBQ-EF) and Emotional overeating (CEBQ-EOE)) increased cardiometabolic risks (e.g. CEBQ-FR: boys: OR = 2.50, 95% CI 1.45; 4.32, girls: OR = 2.33, 95% CI 1.46; 3.71). CEBQ-EF had stronger effects in boys, while CEBQ-EOE was positively associated with cardiometabolic risk among girls. When adjusting for BMIz at 7y, associations did not remain significant. Appetitive behaviors were also associated with isolated cardiometabolic parameters; the strongest association being with waist circumference. Conclusions Appetitive behaviors at 7-years are associated with cardiometabolic risk at age 10. While ‘food avoidant’ behaviors protect against cardiometabolic risk and ‘food approach’ behaviors increase cardiometabolic risk, these associations are largely dependent of child's adiposity.